Community Health Education for Health Crisis Management: The Case of COVID-19 in Cameroon - Mbah, Marcellus; Bang, Henry; Ndi, Humphrey; Ndzo, Judwin Alieh (Community Health Equity Research & Policy, 2023)
The current coronavirus disease 2019 (COVID-19) pandemic has led Cameroon’s government to implement public health measures aimed at preventing its spread. This paper investigates how community health education on the virus was being carried out, what gaps exist and what further action could be taken. A survey instrument was used to gather data among a total of 179 Cameroonians recruited via opportunistic and snowball sampling methods. According to our findings, gaps exist. These include the need for adequate community health education on COVID-19, maximising multilingualism and indigenous cultural assets and disbanding misconceptions on the pandemic, as well as stigmatisation. The paper culminates by underlining the significance of an integrated approach to confront the pandemic. This approach captures the need to frame but also firm up community health education architecture on COVID-19 that captures inputs from different stakeholders, including indigenous knowledge holders, for collective wellbeing.
KerkoCite.ItemAlsoKnownAs: 10.1177/0272684X211031106 5072953:JRMK8IXQ openalex: W3174855276
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; oa:keyword:health crisis management; oa:sdg:3 Good health and well-being; oa:topic:T10410 Modeling the Dynamics of COVID-19 Pandemic; oa:topic:T10833 Factors Affecting Vaccine Hesitancy and Acceptance; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes